Enhancing magnetic hyperthermia: Investigating iron oxide nanoparticle coating and stability - Joana Santos; Jorge Carvalho Silva; Manuel A. Valente; Tânia Vieira; Paula I.P. Soares (Next Nanotechnology)
Cancer treatment research focuses on overcoming the limitations of conventional treatment methods, especially in addressing treatment-resistant malignancies. Magnetic hyperthermia (MH) is an innovative approach that uses superparamagnetic iron oxide nanoparticles (SPIONs) to increase the temperature locally, triggering cancer cell death. However, challenges related to the SPIONs coating impact their stability and MH heating mechanism, hindering its clinical adoption. This work explores diverse SPIONs coating options - oleic acid (OA), dimercaptosuccinic acid (DMSA), and (3-aminopropyl)triethoxysilane (APTES), to improve SPIONS stability under storage while keeping their heating capacity. OA- and DMSA-coated SPIONs, both negatively charged NPs, exhibited similar behavior in protein corona formation and MH tests. The heating capacity of the three types of SPIONs was maintained after 1 month of storage; however, these values significantly decreased to about 60 % of the initial value after 6 months. APTES-coated SPIONs displayed higher protein corona formation, mainly related to the positively charged surface. Interaction studies with three cell lines (fibroblasts, melanoma, and macrophages) revealed enhanced internalization of APTES-coated SPIONs. Only APTES-coated SPIONs achieved therapeutic temperatures in MH assays, reducing melanoma cell viability significantly. The study underscores the importance of nanoparticle surface modifications and the complexity of factors influencing treatment efficacy. Further research is essential for a better understanding of the cell death mechanism induced by MH and for its clinical translation.